AB1067 CASE OR FAMILY?FROM 2 CHINESE FCAS3 CHILDREN WITH PLCG2 MUTATION TO THEIR FAMILIES. (13th June 2020) - Wang, W.; Yang, S.; Yu, Z.; Wei, M.; Zhong, L.; Song, H.
Abstract : Background: Familial cold autoinflammatory syndrome 3 (FCAS3) is an autoinflammatory disease (AID) caused by mutation of the PLCG2 gene, which has not been reported in China. We will report 2 cases of Chinese FCAS3 patients with no claimed family history, but we found the same mutations in a parent during their genetic analysis. After further inquiry of the parent's medical history, we confirmed that actually, they were two FCAS3 families. Through a literature review, we found that the clinical features of Chinese patients are milder than foreign countries, and their symptoms are concealed and may be ignored, resulting in mistakes in family history collecting. Objectives: To summarize the genetic and clinical features of Chinese FCAS3 patients and to provide diagnostic recommendations for the disease. Methods: Two suspected AID children with recurrent fever and urticaria were enrolled in this study. Clinical data and family history were collected, and genetic analysis was performed by next-generation sequencing (PID panel or WES) and Sanger-based validation. Literature was reviewed from PubMed, CNKI, and Wanfang Database. Results: The two children were both diagnosed to be FCAS3 with PLCG2 mutation. The clinical manifestations of 2 children were recurrent fever, urticaria, and increased ESR and CRP. Case 1 has a paternal, and Case 2 has a maternal heterozygous mutation in the PLCG2 gene, while both had claimed without a family history. Further inquiry showed the two parents used to have a fever with urticaria. By comparing with foreign literature, we found our patients were milder than abroad patients. Large fragment deletions were relatively more common in foreign patients. Conclusion: We reported the case of FCAS3 in China for the first time. Their genotype and phenotype were different from foreign patients. Their symptoms are mild, and heterozygous mutations are more common than foreign patients, which are the main differences. The difference in mutation type may be the reason for different clinical manifestations. Besides, both two families showed a trend of more severe clinical features in the next generation. As the symptoms of the elders were not obvious and may be ignored, it caused trouble for the genetic diagnosis. Therefore, family history should be collected carefully. For rashes and fevers, which are not too severe in overall symptoms, care should be taken about the possibility of AIDs. Genetic testing can help to make a definite diagnosis. References: [1]Pathak S, Mcdermott M F, Savic S. Autoinflammatory diseases: update on classification diagnosis and management[J]. Journal of Clinical Pathology, 2017, 70(1):1-8. [2]Broderick, L., Hereditary Autoinflammatory Disorders: Recognition and Treatment. Immunol Allergy Clin North Am, 2019. 39(1):13-29. [3]Milner, Joshua D. PLAID: A Syndrome of Complex Patterns of Disease and Unique Phenotypes[J]. Journal of Clinical Immunology, 2015, 35(6):527-530. [4]Picard C, Gaspar H B, Al-Herz W, et al. International Union of Immunological Societies: 2017 Primary Immunodeficiency Diseases Committee Report on Inborn Errors of Immunity[J]. Journal of Clinical Immunology, 2017, 38(Suppl 1):96-128. [5]Ombrello M J, Remmers E F, Sun G, et al. Cold Urticaria, Immunodeficiency, and Autoimmunity Related to PLCG2 Deletions[J]. New England Journal of Medicine, 2012, 366(4):330-8. [6]Zhou Q, Lee GS, Brady J, et al. A Hypermorphic Missense Mutation in PLCG2, Encoding Phospholipase Cγ2, Causes a Dominantly Inherited Autoinflammatory Disease with Immunodeficiency[J]. American Journal of Human Genetics, 2012, 91(4). [7]Neves, J.F., et al., Novel PLCG2 Mutation in a Patient with APLAID and Cutis Laxa. Front Immunol, 2018. 9: 2863. [8]Mcdermott M F, Aksentijevich I, Galon J, et al. Germline mutations in the extracellular domains of the 55 kDa TNF receptor, TNFR1, define a family of dominantly inherited autoinflammatory syndromes[J]. Cell, 1999, 97(1):133-144. Disclosure of Interests: None declared